Sense of Purpose Promotes Resilience to Cognitive Deficits Attributable to Depressive Symptoms - Lewis, Nathan A.; Hill, Patrick L. (Frontiers in Psychology, 2021)
Objective: Individuals higher in depressive symptoms commonly present with neuropsychological deficits including poorer memory performance. Sense of purpose in life has been shown to promote resilience to cognitive impairment in older adulthood, but it is unclear whether it may also protect against cognitive deficits associated with higher depressive symptoms. Method: Cognitive functioning among 4599 older American adults (Mage = 74.33 years, range = 65 – 104 years, 56.84% female) was examined across a 12-year follow-up period. Depressive symptomatology was assessed at each wave using the 8-item Center for Epidemiologic Studies Depression Scale. Multilevel models assessed the influence of depressive symptoms and the interaction with sense of purpose in life on changes in memory performance and mental status. Results: Higher depressive symptoms were associated with poorer memory performance at baseline, but did not predict rate of change over time. A negative interaction was observed between sense of purpose in life and depressive symptoms such that individuals higher in purpose experienced a less negative association between depressive symptoms and baseline memory performance. No significant interaction of sense of purpose and depressive symptoms was observed on mental status. Conclusions: Having a sense of purpose in life may help protect older adults from memory deficits associated with higher depressive symptoms. The present findings underscore the potential for sense of purpose to promote cognitive reserve in older adulthood, allowing individuals to maintain cognitive performance in the face of accruing neurological insults.